Petrography of the Nimun and Baca pottery (Ware Celestún Roja): Can-Balam Ceramic Sphere of the Yucatan Peninsula, Mexico - Obando-Acuña, Luis G. (2016)
ABSTRACT: The ware Celestún Red (of the Nimun and Baca ceramic typologies) is one of the most diagnostic ceramics of the northwestern coast of Mexico’s Yucatan Peninsula and a subject of ongoing debate regarding its distribution and origin. Although ceramics from coastal Campeche and Yucatan have been the focus of years of investigation, scholars still do not know if Celestún Red was manufactured locally during the Late Classic (A.D. 600-900) or was made and exchanged by the regional elite. In this presentation, the authors provide the first petrographic descriptions of Celestún Red, and use them to contribute to a formal definition of the Cambalan Ceramic Sphere defined by Jiménez (2002), Jiménez, Ceballos & Sierra (2006). These petrographic observations show that the detrital components were rhyolite fragments, vitroclastic tuffs, pumice, shards of glass, quartzes, plagioclase, calcite, hematite, magnetite and other minor contributors. The clay matrix is phyllomorphic, with a parallel, rectilinear fabric of fine grains. Granulometrically, the detrital components have been characterized as fine to medium sands. The pastes present evidence of diagenetic processes, most notably porosity in the primary ceramic matrix. These spaces are in some cases filled by secondary calcite deposits.     Evidence of manufacturing was also observed, such as the fractures and bending of the paste that took place to produce the rims of these ceramic objects.